2014
DOI: 10.1186/1748-717x-9-192
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of respiration-induced pancreatic tumor motion based on reference measurement

Abstract: BackgroundTo evaluate pancreatic tumor motion and its dynamics during respiration.Methods and materialsThis retrospective study includes 20 patients with unresectable pancreatic cancer who were treated with stereotactic ablative radiotherapy. An online respiratory tumor tracking system was used. Periodical maximum and minimum tumor positions with respiration in superior-inferior (SI), latero-lateral (LL), and anterior-posterior (AP) directions were collected for tumor motion evaluation. The predictability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Several studies have demonstrated significant effects of the above‐listed immobilization devices in intrafraction motion mitigation, 21 , 23 , 29 , 30 the unconstrained condition was therefore not included in the study, since our goal was to quantify the level of immobilization in the abdomen–pelvis region as a function of patient setup position and selected immobilization devices. It should be noted that the condition “vacuum cushion” cannot be considered an unconstrained condition, since the MR scan was performed with the body matrix coil slightly tightened to the patient thorax and back (supine and prone position, respectively), mimicking the effects of a mild restraining belt.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated significant effects of the above‐listed immobilization devices in intrafraction motion mitigation, 21 , 23 , 29 , 30 the unconstrained condition was therefore not included in the study, since our goal was to quantify the level of immobilization in the abdomen–pelvis region as a function of patient setup position and selected immobilization devices. It should be noted that the condition “vacuum cushion” cannot be considered an unconstrained condition, since the MR scan was performed with the body matrix coil slightly tightened to the patient thorax and back (supine and prone position, respectively), mimicking the effects of a mild restraining belt.…”
Section: Methodsmentioning
confidence: 99%
“…Interfraction variations are determined by anatomical or physiological modifications, which potentially could be managed with pretreatment in‐room imaging and replanning tools (20) . Conversely, intrafraction variations are mainly introduced by periodic anatomical changes, such as breathing motion, especially in the superior–inferior (SI) direction 21 , 22 , 23 , 24 . Specific treatment planning schemes have been designed in order to account for breathing motion (25) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The motion of the pancreas has been shown to preferentially move during respiration 1.5 to 2.0 cm in superior-inferior direction and 0.5 to 1.0 cm radially. 13,14 Respiratory-gating treatment is a technique where the beam is delivered to the tumor at a particular respiratory phase. The advantage of this technique is that the planning margins can be smaller so less normal tissue is irradiated.…”
Section: Target and Critical Organsmentioning
confidence: 99%